A regulamentação das apostas esportivas no Brasil - Val, Fernando de Arruda do (2022)
The present end-of-course paper addresses the regulation of sports betting, especially regarding the implications of Law 13.756/2018, sanctioned by President Michel Temer on December 12, 2018, and the regulatory decree with excpectation of being sanctioned in December of the present year 2022. To this end, firstly, the history of sports betting in Brazil and in the world will be addressed, in addition to the pathology arising from the gambling of sports betting. Then, secondly, Law 13.756/2018 will be addressed, with a legal-economic analysis from the perspective of the Brazilian scenario. Third, the main sub-themes of sports betting regulation, which may have huge impacts in the coming years, will be addressed. Fourth, the topic of Sports Betting Taxation will be addressed, undoubtedly the most controversial topic. And finally, the great loss of Brazil without the regulation will be exposed and the conclusion